Blood Substitutes and Oxygen Therapeutics: A Review. (January 2021) - Jahr, Jonathan S.; Guinn, Nicole R; Lowery, David R.; Shore-Lesserson, Linda; Shander, Aryeh
Abstract : Despite the exhaustive search for an acceptable substitute to erythrocyte transfusion, neither chemical-based products such as perfluorocarbons nor hemoglobin-based oxygen carriers have succeeded in providing a reasonable alternative to allogeneic blood transfusion. However, there remain scenarios in which blood transfusion is not an option, due to patient's religious beliefs, inability to find adequately cross-matched erythrocytes, or in remote locations. In these situations, artificial oxygen carriers may provide a mortality benefit for patients with severe, life-threatening anemia. This article provides an up-to-date review of the history and development, clinical trials, new technology, and current standing of artificial oxygen carriers as an alternative to transfusion when blood is not an option.